Adjacent channel rejection analysis due to channel select filter in RF superheterodyne receiver of WLAN IEEE 802.11a - Shairi, N. A. (2012)
In this paper, an analysis of adjacent channel rejection (ACR) due to channel select filter (CS filter) in RF superheterodyne receiver is presented. The ACR analysis is based on IEEE 802.11a standard at 5.8 GHz frequency band. In early stage of any RF receiver design for Wireless Local Area Network (WLAN) Orthogonal Frequency Division Multiplexing (OFDM) system, a system level analysis of ACR is needed prior to any CS filter design. This is important since the IEEE 802.11a uses adaptive data rates between 6 Mbps and 54 Mbps which gives different ACR level for CS filter. Hence, ACR analysis can determine out-of-band attenuation level of CS filter for RF superheterodyne receiver. This analysis is performed in a simulation software. As result, it shows that higher out-of-band attenuation level is required in CS filter for low data rate (e.g. 6 Mbps) compared to high data rate (e.g. 54 Mbps). Thus, the 30 dB attenuation level at adjacent channels in the CS filter is suggested for the RF superheterodyne receiver in order to meet ACR performance based on IEEE 802.11a standard.